Regioselective 3-O-Substitution of Unprotected Thiodigalactosides: Direct Route to Galectin Inhibitors - Vašíček, Tomáš; Spiwok, Vojtěch; Červený, Jakub; Petrásková, Lucie; Bumba, Ladislav; Vrbata, David; Pelantová, Helena; Křen, Vladimír; Bojarová, Pavla (Chemistry (Weinheim an der Bergstrasse, Germany), 2020)
The synthesis of tailored bioactive carbohydrates usually comprises challenging (de)protection steps, which lowers synthetic yields and increases time demands. We present here a regioselective single-step introduction of benzylic substituents at 3-hydroxy groups of β-d-galactopyranosyl-(1→1)-thio-β-d-galactopyranoside (TDG) employing dibutyltin oxide in good yields. These glycomimetics act as inhibitors of galectins-human lectins, which are biomedically attractive targets for therapeutic inhibition in, for example, cancerogenesis. The affinity of the prepared glycomimetics to galectin-1 and galectin-3 was studied in enzyme-linked immunosorbent (ELISA)-type assays and their potential to inhibit galectin binding on the cell surface was shown. We used our original in vivo biotinylated galectin constructs for easy detection by flow cytometry. The results of the biological experiments were compared with data from molecular modeling with both galectins. The present work reveals a facile and elegant synthetic route for the preparation of TDG-derived glycomimetics that exhibit differing selectivity and affinity to galectins depending on the choice of 3-O-substitution.
Keywords: galektin 3; thiogalaktosidy; Carbohydrates; Blood Proteins; Thiogalactosides; carbohydrates; Galactose; Galectin 3; galektin 1; Galectins; molekulární modely; Galectin 1; Models, Molecular; krevní proteiny; lidé; inhibitors; Humans; sacharidy; molecular modeling; glycomimetics; galektiny; glycosides; galaktosa